PHENOTYPIC FEATURES OF CELLS IN URINARY SEDIMENT OF PATIENTS WITH NON-INVASIVE BLADDER CANCER - R. A. Zukov; E. V. Slepov; E. V. Semenov; L. M. Kurtasova (Сибирский онкологический журнал, 2017)
More than 430,000 new cases of bladder cancer are diagnosed every year in the world, and approximately 70–80 % of patients present with non-invasive disease. To improve the effectiveness of early detection of bladder cancer, high sensitivity diagnostic tools should be used. In our study we used flow cytometry to determine surface markers in urinary sediment cells of patients with bladder cancer. The analysis of the phenotypic features of urinary sediment cells showed an increase in the relative content of CD13+ cells in patients with non-invasive bladder cancer in comparison with the control group. In addition, there was a 4.8-fold increase in cells expressing CD15 surface antigen (p<0.001) and 4.9-fold increase in cells expressing CD45 surface antigen (p<0.001). Considering the fact, that most patients with bladder cancer develop recurrence after treatment, we studied the relationship between the expression level of surface markers of urinary sediment cells and the development of disease recurrence. The absence of differences in the level of CD15+ cells in urinary sediment of patients with recurrent bladder cancer can be explained by the absence of differences in proliferative activity of recurrent and non-recurrent tumors. The higher level of CD13+ cells in patients with recurrent bladder cancer indicates greater depth of tumor invasion. It is obvious that the deeper the tumor invasion into the submucosal layer of the bladder, the greater the likelihood of non-radical transurethral resection and the development of disease recurrence. Thus, the analysis of the level of CD13+ and CD45+ cells in the urinary sediment can provide information on tumor invasion into the bladder submucosal layer and the risk of bladder cancer recurrence.